Reduction of Burn Progression with Topical Delivery of (Anti-Tumor Necrosis Factor-α)-Hyaluronic Acid Conjugates - Sun, Liang Tso (2012)
In this study, we explored whether topical application of antibodies targeting tumor necrosis factor-α (TNF-α) or interleukin-6 (IL-6) conjugated to hyaluronic acid (HA) could reduce the extension of necrosis by modulating inflammation locally in a partial-thickness rat burn model. Partial-thickness to deep partial-thickness burn injuries present significant challenges in healing, as these burns often progress following the initial thermal insult, resulting in necrotic expansion and increased likelihood of secondary complications. Necrotic expansion is driven by a microenvironment with elevated levels of pro-inflammatory mediators, and local neutralization of these using antibody conjugates could reduce burn progression. Trichrome-stained tissue sections indicated the least necrotic tissue in (anti-TNF-α)-HA treated sites, while (anti-IL-6)-HA treated sites displayed similar outcomes to saline controls. This was confirmed by vimentin immunostaining, which demonstrated that HA treatment alone reduced burn progression by nearly 30%, but (anti-TNF-α)-HA reduced it by approximately 70%. At all time points, (anti-TNF-α)-HA treated sites showed reduced tissue levels of IL-1β compared to controls, suggesting inhibition of a downstream mediator of inflammation. Decreased macrophage infiltration in (anti-TNF-α)-HA-treated sites compared to controls was elucidated by immunohistochemical staining of macrophages, suggesting a reduction in overall inflammation in all time points. These results suggest that local targeting of TNF-α may be an effective strategy for preventing progression of partial-thickness burns.